Impact of a Pharmacy-Cardiology Collaborative Practice on Dofetilide Safety Monitoring. (January 2017) - Quffa, Lieth H.; Panna, Mark; Kaufmann, Michael R.; McKillop, Matthew; Dietrich, Nicole Maltese; Franck, Andrew J.
Background: Limited studies have been published examining dofetilide's postmarketing use and its recommended monitoring.Objective: To evaluate the impact of a collaborative pharmacy-cardiology antiarrhythmic drug (AAD) monitoring program on dofetilide monitoring.Methods: This retrospective cohort study was performed to assess if a novel monitoring program improved compliance with dofetilide-specific monitoring parameters based on the Food and Drug Administration's Risk Evaluation and Mitigation Strategy.Results: A total of 30 patients were included in the analysis. The monitoring parameters evaluated included electrocardiogram, serum potassium, serum magnesium, and kidney function. The primary outcome evaluated was the composite of these dofetilide monitoring parameters obtained in each cohort. In the standard cohort, 245 of 352 (69.6%) monitoring parameters were completed versus 134 of 136 (98.5%) in the intervention group ( P < 0.05).Conclusion: A collaborative pharmacy-cardiology AAD monitoring program was associated with a significant improvement in dofetilide monitoring. This improvement could potentially translate into enhanced patient safety outcomes, such as prevention of adverse drug reactions and decreased hospitalizations.